2022
DOI: 10.1097/gox.0000000000004364
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on a Career in Plastic Surgery: A National Survey of Retired Surgeons

Abstract: Introduction: Retired plastic surgeons can provide valuable insights for the greater plastic surgery community. The purpose of this study was to gather demographics, personal reflections, and advice for a career in plastic surgery from retired American plastic surgeons. Methods: An email survey was distributed to 825 members of the American Society of Plastic Surgeons during September 2021. The survey distribution was designed to engage members of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…6,11 This contradicts the norm for plastic and orthopedic surgery as 89.7% and 73.5% of all surgeons in these fields practice in a private setting, respectively. 22,23 These findings also challenge traditional stereotypes which insinuate physicians obtain MBAs to pivot into a more lucrative career and suggest many surgeons may pursue an MBA to instead further their academic career. 4 This assertion is further supported by Lee and Patel who found financial gain motivated 25% and 0% of surgeons to pursue an MBA, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…6,11 This contradicts the norm for plastic and orthopedic surgery as 89.7% and 73.5% of all surgeons in these fields practice in a private setting, respectively. 22,23 These findings also challenge traditional stereotypes which insinuate physicians obtain MBAs to pivot into a more lucrative career and suggest many surgeons may pursue an MBA to instead further their academic career. 4 This assertion is further supported by Lee and Patel who found financial gain motivated 25% and 0% of surgeons to pursue an MBA, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…27 Although the impact that fellowship training will have on a physician's career goals is one of the main deciding factors, consideration should also be given to other outcomes, such as career satisfaction. 19,28 DeSerres et al demonstrated high career satisfaction amongst attendings, of which nearly 90% completed a fellowship following residency training. 19 Further studies are warranted to assess whether graduating PRS residents consider these factors when deciding to pursue a fellowship.…”
Section: Discussionmentioning
confidence: 99%